2001
DOI: 10.1139/z01-113
|View full text |Cite
|
Sign up to set email alerts
|

Pretty patterns but a simple strategy: predator-prey interactions between juvenile herring and Atlantic puffins observed with multibeam sonar

Abstract: Predator-prey interactions between Atlantic puffins (Fratercula arctica) and newly metamorphosed herring (Clupea harengus) were studied in the Lofoten-Røst area in northern Norway using a high-resolution multibeam sonar system. Attacks from diving puffins and predatory fish induced massive predator-response patterns at the school level, including bend, vacuole, hourglass, pseudopodium, herd, and split. All patterns have previously been observed, using the same sonar, in schools of adult herring attacked by gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 36 publications
4
50
0
2
Order By: Relevance
“…While diving birds have been shown to be de tectable using sonar , Axelsen et al 2001, Brierley & Fernandes 2001, and Axelsen et al (2001) used acoustics to qualitatively examine the relationship be tween seabird predators and their prey, this is the first published account using quantitative fisheries acous tics techniques to examine sea bird−prey interactions. Se veral advantages of using fisheries acous tics techniques are apparent: (1) the approach is non-invasive; (2) in addition to bird horizontal position, it allows the depth of birds to be measured up to about 200 m; (3) it is not limited by visual conditions like fog and darkness; (4) it excludes nondiving birds that are not actively foraging; (5) ple sizes, allowing population le vel res ponses to be ob served (N = 5140 in the present study); and (6) it allows simultaneous sampling of birds and the quantification of the type, depth, distribution, and density of potential prey, permitting the horizontal and vertical overlap between predator and prey to be examined at the same resolution and scale.…”
Section: Detecting Diving Birdsmentioning
confidence: 99%
“…While diving birds have been shown to be de tectable using sonar , Axelsen et al 2001, Brierley & Fernandes 2001, and Axelsen et al (2001) used acoustics to qualitatively examine the relationship be tween seabird predators and their prey, this is the first published account using quantitative fisheries acous tics techniques to examine sea bird−prey interactions. Se veral advantages of using fisheries acous tics techniques are apparent: (1) the approach is non-invasive; (2) in addition to bird horizontal position, it allows the depth of birds to be measured up to about 200 m; (3) it is not limited by visual conditions like fog and darkness; (4) it excludes nondiving birds that are not actively foraging; (5) ple sizes, allowing population le vel res ponses to be ob served (N = 5140 in the present study); and (6) it allows simultaneous sampling of birds and the quantification of the type, depth, distribution, and density of potential prey, permitting the horizontal and vertical overlap between predator and prey to be examined at the same resolution and scale.…”
Section: Detecting Diving Birdsmentioning
confidence: 99%
“…First, favourable conditions early in life can result in high survival but reduced growth and condition due to reduced per capita food intake, as a density-dependent effect (Barros and Toresen 1998). Second, strong year-classes, characterised by reduced growth and condition indices (Toresen 1990;Holst 1996) may suffer less predation and exploitation mortality due to the dilution effect (Axelsen et al 2001). Alternatively, if skipped 375 reproduction is not restricted to the second spawning season but also occurs in older spawners, then the inverse relationship between condition and survival might even be the result of skipped reproduction per se.…”
mentioning
confidence: 99%
“…Axelsen et al 2001, Benoit-Bird & Au 2003. Analysis of underway data showed that more fish were correlated with more of the same-sized holes, while bigger fish were correlated with bigger individual holes.…”
Section: Discussionmentioning
confidence: 99%
“…Prey in benthic systems have been found to aggregate into discrete patches as a mechanism to avoid predators (see, for example, Hildrew & Townsend 1982), changing not only the prey animals' density but also their distribution. While numerous studies in pelagic systems have investigated the effects of prey distribution on predator behavior, and studies in benthic habitats have revealed the significant impacts predators can have on prey distribution (see a review in Cooper et al 1990), relatively few field studies outside the schooling fish literature have investigated the effects of predator behaviors on prey distribution in pelagic systems (Orr 1981, Axelsen et al 2001, De Robertis et al 2003, Benoit-Bird & Au 2009). These interactions can have effects on individual animals, their competitors and predators, as well as the measurements obtained of them and their environment.…”
Section: Introductionmentioning
confidence: 99%